Calf Perforator Flaps: A Freestyle Solution for Oral Cavity Reconstruction. Issue 2 (February 2017) - Molina, Alexandra R.; Citron, Isabelle; Chinaka, Fungayi; Cascarini, Luke; Townley, William A.
Abstract : Background: Reconstruction of oral cavity defects requires a thin, pliable flap for optimal functional results. Traditional flap choices are imperfect: the anterolateral thigh flap is excessively thick, whereas the radial forearm flap has a poor donor site. The authors therefore favor calf perforator flaps such as the medial sural artery perforator flap to provide thin tissue with an acceptable donor site. This two-part study aims to demonstrate their suitability for intraoral reconstruction. Methods: In the radiologic part of the study, the authors compared thigh and calf tissue thickness by examining lower limb computed tomographic scans of 100 legs. For their clinical study, they collected data prospectively on 20 cases of oral cavity reconstruction using calf perforator flaps. Results: The mean thickness of the calf tissue envelope was significantly less than that of the thigh (8.4 mm compared with 17 mm) based on computed tomographic analysis. In the clinical study, a medial sural artery perforator was used in the majority of cases (17 of 20). The mean pedicle length was 10.2 cm and the mean time to raise a flap was 85 minutes. There were no flap losses. One patient was returned to the operating room for management of late hematoma and wound dehiscence. Conclusions: Calf perforator flaps provide ideal tissue for intraoral reconstruction and are significantly thinner than anterolateral thigh flaps. In addition to medial sural artery perforator flaps, the authors raised both sural and soleal artery perforator flaps in this series. Opportunistic use of the calf donor site allows the harvest of thin tissue with minimal donor-site morbidity. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.